PENGARUH POLA DIET TERHADAP KEJADIAN DISPEPSIA FUNGSIONAL DI RSUD KOTA TIDORE KEPULAUAN - Ferdian Hadiyat; Abd Hakim Husen; Asyura Abdullah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
The habit of consuming foods and beverages such as spicy or sour foods, drinking tea or coffee and other carbonated drinks can increase the risk of developing dyspepsia syndrome. This study aims to determine the relationship between dietary patterns and the incidence of dyspepsia. This cross-sectional study involved 134 people who were carried out at the Internal Medicine Polyclinic of the Tidore Kepulauan City Hospital. The results showed that the dominant type of food in the spicy category was 59 people (44%), and the most preferred type of beverage was coffee as many as 71 people (53%). The results of the chi square test obtained a very significant P-value for the variables of types of drinks and types of food, namely <0.05. The conclusion of the study is that types of foods such as spicy, fatty and sour causes an increase in the incidence of dyspepsia, as well as drinks such as coffee and tea trigger an increase in stomach acid.